PENGEMBANGAN MEDIA INTERAKTIF VIDEO-QUIZ PADA MATA PELAJARAN IPAS MATERI BERKENALAN DENGAN BUMI KITA UNTUK MENINGKATKAN RASA INGIN TAHU MURID KELAS V - Afifah Intan Pauziyyah; Bagas Kurnianto (Universitas Negeri Medan, 2026)
The primary objective of this research is to develop a viable and effective interactive video-quiz medium based on the Educaplay platform for use in fifth-grade IPAS instruction on the topic “Let’s Get to Know Our Earth.” The research design employed is research and development (R&D), utilizing the 4D model, which comprises the define, design, develop, and disseminate stages. Data collection techniques included observation, interviews, questionnaires, and tests. The media validation results from media experts and subject matter experts indicated that the developed media met the “highly suitable” criteria, with a 96% approval rate from media experts and a 94% approval rate from subject matter experts. The response rates from teachers (92%) and students (91%) regarding the media also fell into the “very good” category, thus the media was deemed practical for use in instruction. Student learning outcomes showed an improvement, as evidenced by a pretest average score of 52—which was still relatively low—and a significant increase to 81 on the posttest following the use of the media. The results of the t-test data analysis showed a value (Sig. 2-tailed) < 0.05, so it can be said that there is a significant difference between learning outcomes before and after the use of the media. Meanwhile, the results of the N-Gain test indicate the media’s effectiveness is in the “fair” category. Thus, it can be concluded that the interactive video-quiz media based on the Educaplay platform is suitable and effective for enhancing students’ curiosity and learning outcomes